P285 Crohn's disease overall severity is predictive of disabling disease: Disease severity index evaluation. (16th January 2018) - Pereira Rodrigues, J; Sousa, M; Silva, J C; Freitas, T; Silva, A P; Rodrigues, A; Carvalho, J
Abstract: Background: Current evidence suggests that a cross-sectional assessment of Crohn's disease (CD) activity at a certain time is reductive. Recently, a group of experts developed the Disease Severity Index (DSI) (Siegel CA et al., 2016) that evaluates overall disease severity through a snapshot and a longitudinal assessment of CD. We aimed to evaluate the relation between DSI and disabling DC. Methods: Retrospective, single-centre analysis of all ≥18 year-old CD patients, observed at outpatient clinic from January to November 2013, with ≥4 years of follow-up. DSI at the appointment date was determined and its relation with disabling DC assessed. Disabling CD was defined as the occurrence of at least one of the following: ≥2 steroid course requirements/year, steroid dependency or refractoriness; need to switch or escalate dosages of immunomodulators and/or anti-TNF drugs; ≥2 hospitalisations (excluding the index episode, if applicable); new events such as strictures, penetrating disease or anal disease; ≥1 surgeries (excluding the index surgery, if applicable). Results: 123 patients were included, 53.7% ( n = 66) male, with mean age 41.7 ± 13.7 years and mean age at diagnosis 32.7 ± 12.6 years. Ileal/ileocolonic disease was present in 82.9% ( n = 102) of patients, upper gastrointestinal (GI) involvement in 16.3% ( n = 20), a penetrating phenotype in 25.2% ( n = 31) and perianal disease in 29.3% ( n = 36). Mean follow-up was 52.7 ± 5.5 months. A disabling disease course was identified in 56.1% ( n = 69) patients: steroid therapy in 22.8% ( n = 28), immunomodulators/anti-TNF switch or dose escalation in 35.0% ( n = 80), hospitalisation in 17.1% ( n = 21), new events in 23.6% ( n = 29) and surgery in 11.5% ( n = 14). Ileal/ileocolonic disease, upper GI disease, perianal disease, abdominal pain, frequency of loose stools, anorectal symptoms, presence of fistula or stricture, perianal abscess, impact on daily activities, anaemia, C reactive protein elevation and mucosal lesions were associated with disabling disease ( p < 0.05). On multivariate analysis, adjusted for gender and age at diagnosis, upper GI disease, frequency of loose stools and mucosal lesions were independently associated with disabling disease ( p < 0.05; r = 0.52). DSI ranged from 0–60 (mean = 21.2 ± 13.7) and was significantly higher in the group of patients with disabling disease (27.6 ± 12.8 vs. 13.0 ± 9.9, p < 0.05). The area under the ROC curve for DSI prediction of disabling CD was 0.82 (95% CI 0.74–0.89, p < 0.05). Conclusions: Our data support Disease Severity Index as a predictive method of disabling Crohn's disease. Routine use of this score will allow identification of patients at a higher risk of worse outcome so that appropriate intensive treatment can be initiated or optimised.